How Corporate Social Responsibility and Brand Image Shape Partner Satisfaction: The Mediating Role of Brand Equity - Satriyo Agung Nugroho; Sefnedi Sefnedi; Reni Yuliviona (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) and brand image on partner satisfaction, both directly and indirectly through brand equity as a mediating variable. The research was conducted at PT Pelabuhan Indonesia (Persero) Regional 2 Teluk Bayur by involving all active partners totaling 125 companies using a census method. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (PLS-SEM). The results show that CSR, brand image, and brand equity have a positive and significant effect on partner satisfaction. CSR also has a positive and significant influence on brand image and brand equity. Furthermore, brand equity is proven to mediate the relationship between CSR and brand image on partner satisfaction. The results of the Importance–Performance Map Analysis (IPMA) indicate that CSR is the variable with the highest level of importance in improving partner satisfaction compared to brand image and brand equity. The findings imply that integrating CSR into business strategy, along with consistently strengthening brand image and brand equity, is essential to support the sustainability of partnership relationships in the port sector.